2017
DOI: 10.1097/pap.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

What is New in Gastrointestinal Stromal Tumor?

Abstract: The classification “gastrointestinal stromal tumor” (GIST) became commonplace in the 1990s and since that time various advances have characterized the GIST lineage of origin, tyrosine kinase mutations, and mechanisms of response and resistance to targeted therapies. In addition to tyrosine kinase mutations and their constitutive activation of downstream signaling pathways, GISTs acquire a sequence of chromosomal aberrations. These include deletions of chromosomes 14q, 22q, 1p, and 15q, which harbor putative tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 62 publications
1
87
0
3
Order By: Relevance
“…Drug resistance and tumor recurrence are most of the concerns in clinical practices of GIST . To deal with these, our study has revealed a novel tumor promoter, DKK4, which was upregulated by activated Wnt pathway in high‐risk GIST, promoting tumor progression via forming the immune suppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug resistance and tumor recurrence are most of the concerns in clinical practices of GIST . To deal with these, our study has revealed a novel tumor promoter, DKK4, which was upregulated by activated Wnt pathway in high‐risk GIST, promoting tumor progression via forming the immune suppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance and tumor recurrence are most of the concerns in clinical practices of GIST. 42,43 To deal with these, our study has revealed a novel tumor promoter, DKK4, which was upregulated by activated Wnt pathway in high-risk GIST, promoting tumor progression via forming the immune suppressive microenvironment. Owing to necessity of immune cells participation in drug effects, DKK4 partially accounts for the weak sensitivity to RTK inhibitor in some cases, and can be recognized as a therapeutic target to enhance drug effects.…”
Section: Discussionmentioning
confidence: 99%
“…CCND2 ampli cation and amino acid missense mutation at position 932 of exon 19 of the PTCH1 gene was found. These novel two changes have not previously been reported in GISTs or other SDH-associated tumors [1,3,10,17]. CCND2 belongs to the highly conserved cyclin family, forms a complex with CDK4 or CDK6 and functions as a regulatory subunit of the complex, whose activity is required for cell cycle G1/S transition.…”
Section: Case Presentationmentioning
confidence: 65%
“…GIST was mistaken for schwannomas, leiomyomas or leiomyosarcomas until the introduction of ultrastructural, immunohistochemical, and molecular biological techniques, which uncovered that GIST originated from myenteric nervous system [25] , and ICCs were further suggested to be the cells of origin [26] . Subsequently, gain-of-function mutations in the tyrosine kinase receptor KIT and platelet-derived growth factor receptor-α (PDGFRA) were groundbreakingly found as the main oncogenic driver in GIST [27,28] , which encouraged the development of GIST targeted therapies [5] . In recent researches, Etwenty-six (ETS) variant 1 (ETV1) was also reported to overexpress in GIST and enhance the expression of KIT when binding target genes [1,29] .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of GIST has increased in the recent years, possibly related to the rapid development of endoscopic technology [1] . GIST can occur anywhere throughout the GI tract, stomach and small intestine are the most common site, followed by colon, rectum, esophagus [4,5] .…”
Section: Introductionmentioning
confidence: 99%